2005
DOI: 10.1385/criai:29:3:307
|View full text |Cite
|
Sign up to set email alerts
|

Uncovering the Hidden Potential of Intravenous Immunoglobulin as an Anticancer Therapy

Abstract: Intravenous immunoglobulin (IVIg) is a safe preparation made from human plasma. The original concept of IVIg as an anticancer drug was built up over the years, after numeral reports were accumulated indicating cancer regressions after IVIg administration. Because IVIg is basically an established remedy for immunodeficiencies and several autoimmune diseases, the association between beneficial effects in cancer patients after IVIg was first seen in patients who had both cancer and autoimmune or immunodeficiency … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 15 publications
0
18
0
Order By: Relevance
“…The coexistence of autoimmune pathologies and cancer has previously provided evidence that IVIg therapy promotes regression of cancer in patients with chronic lymphatic leukemia, Kaposi's sarcoma, and melanoma (42). Given the importance of the polarization of TAM for tumor progression and dissemination (37), our results establish a sequential link between the IVIg ability to modulate macrophage polarization and its antitumor effect, suggesting that the proinflammatory activities of IVIg might also be therapeutically useful in pathologies (2) or IVIg treated, either with or without clodronate liposome-mediated depletion of macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…The coexistence of autoimmune pathologies and cancer has previously provided evidence that IVIg therapy promotes regression of cancer in patients with chronic lymphatic leukemia, Kaposi's sarcoma, and melanoma (42). Given the importance of the polarization of TAM for tumor progression and dissemination (37), our results establish a sequential link between the IVIg ability to modulate macrophage polarization and its antitumor effect, suggesting that the proinflammatory activities of IVIg might also be therapeutically useful in pathologies (2) or IVIg treated, either with or without clodronate liposome-mediated depletion of macrophages.…”
Section: Discussionmentioning
confidence: 99%
“…Although not wishing to be bound by any particular theory, we propose that the IVIg inhibits metastases by one or more of the following mechanisms (reviewed in Ref. 20). First, our previous in vitro studies revealed that IVIg led to significant enhancement of IL‐12 cytokine secretion by mononuclear cells.…”
Section: Discussionmentioning
confidence: 99%
“…Considering the fact that tissues damaged by autoimmune dysfunction and by cancer have similar characteristics (e.g. chronic innate immune cell infiltration, tissue remodeling, angiogenesis, altered cell survival pathways) [48], it seems probable that similar IC effector pathways are involved in pathogenesis of both diseases.…”
Section: Fcgr and C5a Are Key Regulators Of Ic-mediated Inflammationmentioning
confidence: 99%